Impact of viral hepatitis aetiology on survival outcomes in hepatocellular carcinoma: A large multicentre cohort study. Issue 11 (9th June 2017) - Mgaieth, S.; Kemp, W.; Gow, P.; Fink, M.; Lubel, J.; Nicoll, A.; Gazzola, A.; Hong, T.; Ryan, M.; Knight, V.; Dev, A. T.; Sood, S.; et al.
Summary: While HBV and HCV are risk factors for HCC, uncertainty exists as to whether these viral infections have prognostic significance in HCC. Thus, we compared the overall survival of patients with HBV, HCV and nonviral HCC, and evaluated whether the presence of HBV and HCV predicts patient outcomes. We conducted a multicentre study of HCC cases diagnosed at six Melbourne tertiary hospitals between Jan 2000‐Dec 2014. Patient demographics, liver disease and tumour characteristics and patient outcomes were obtained from hospital databases, computer records and the Victorian Death Registry. Survival outcomes were compared between HBV, HCV and nonviral hepatitis cases and predictors of survival determined using Cox proportional hazards regression. There were 1436 new HCC cases identified including 776 due to viral hepatitis (HBV 235, HCV 511, HBV‐HCV 30) and 660 from nonviral causes. The median survival of HBV, HCV and nonviral HCC patients was 59.1, 28.4 and 20.9 months, respectively ( P <.0001). On multivariate analysis, independent risk factors for survival included HCC aetiology, gender, BCLC stage, serum AFP, total number and size of lesions, and serum creatinine and albumin. After adjusting for these and method of detection, HBV remained an independent predictor of improved overall survival when compared to both nonviral (HR 0.60%, 95% CI 0.35‐0.98; P =.03) and HCV‐related HCC (HR 0.51%, 95% CI 0.30‐0.85; P =.01). In this large multicentre study, HBV is independently associated with improved overall survival compared with HCV and nonviral‐related HCC. Further studies are needed to determine the underlying factor(s) responsible.